(untitled) (Damascus University Journal for legal sciences, 2025)
This research sheds light on the issue of documenting the marriage contract in the Sharia courts, which is taken over by the judge appointed by the guardian, and strife and calamities prevailed in some Arab countries, and this resulted in documenting the marriage contract outside the Sharia courts, which led to the loss of women’s rights and their diaspora. Many young people have documented the marriage contract - fulfilling its conditions and pillars - outside the Sharia courts, then it was lost as a result of the ongoing wars and no news was known about him, and the woman did not know whether the one who proposed to her - then wrote the marriage contract outside the Sharia courts - was alive or separated? Do you wait for many years for him to come back and then miss the train of marriage, or what do you do? Note that if she had referred her case to the judge, he would have said to her: There is no marriage contract for you that is proven in court, so how can I rule by separation due to absence or harm? The statistics that took place on the aforementioned are alarming, numbering in the thousands, through which Muslim girls lived in unparalleled waste and scattering, but what are the legitimate ways to preserve women’s rights in such countries? And based on the intentional view of the outcome of actions, does the ruling on documenting the marriage contract in the Shari’a courts remain a matter of assignment, or does it rise to the ruling of being obligatory? As a result of this research, it is necessary to document the marriage contract in the Sharia courts, not to stand on the saying of the delegation. In order to preserve the rights of the woman, if the marriage contract was concluded outside the Sharia courts, the woman may take her infallibility in her own hands until the marriage contract is established in the Sharia courts.